The k-Lucas Hyperbolic Functions - Taşçı, Dursun; Azman, Huriye (Communications in Mathematics and Applications, 2014)
In this paper, we introduced and studied an extension of the classical hyperbolic functions. We de…ned k-Lucas hyperbolic functions and studied their hyperbolic and recurrence properties, and investigated the relations between this new k-Lucas hyperbolic functions and the k-Fibonacci hyperbolic functions, which were studied before by Falcon and Plaza. We also studied the quasi-sine k-Lucas functions.